2021
DOI: 10.1049/tje2.12091
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the distribution power system resilience against hurricane events using a bayesian network line outage prediction model

Abstract: Enhancing the grid resilience against hurricane events proactively requires a pre‐disaster system optimization built on accurate system network line outage prediction. In the past, the statistical system level failure predictive model such as generalized linear model (GLM), generalized additive model (GAM), system tree‐based mining model (classification regression tree (CART), Bayesian additive regression model (BART), and the topology‐based system components’ fragility curve (FC)‐Monte Carlo simulation (MCS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…III. The detail explanation of prediction accuracy analysis can be found in [21], [26]. The predicted DSN line's fault scenarios from both the predictive algorithms under hurricane event are leveraged, by the DSO as power system resilience proactive operational planning tool to decrease the expected load loss.…”
Section: Discussion On the Proposed Bn-dsn And Combined Statistical D...mentioning
confidence: 99%
See 4 more Smart Citations
“…III. The detail explanation of prediction accuracy analysis can be found in [21], [26]. The predicted DSN line's fault scenarios from both the predictive algorithms under hurricane event are leveraged, by the DSO as power system resilience proactive operational planning tool to decrease the expected load loss.…”
Section: Discussion On the Proposed Bn-dsn And Combined Statistical D...mentioning
confidence: 99%
“…The prediction accuracy analysis was the focus of the paper. The study demonstrated that the proposed BN-DSN line fault simulated are more accurate DSN line fault prediction when compared with the combined statistical DSN line's FC-MCS-SCENRED predictive model [20], [21]. In [26], the proposed BN-DSN was also applied to a 48-bus DSN to forecast the DSN line's fault scenario leveraging the predicted oncoming hurricane Ewiniar data.…”
Section: Figurementioning
confidence: 97%
See 3 more Smart Citations